Journalism and Journalists’ Vulnerability during COVID-19 Pandemic in Indonesia - Abdul Fadli Kalaloi; Rana Akbari Fitriawan; Reni Nuraeni (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
Journalists are among the workers who continue to engage in journalism activities like news covering despite the COVID-19 pandemic. Journalists facing paradoxical conditions between being productive in news covering and the dangers of virus transmission that can infect at any time. In other hand, journalists need support equipment facilities to avoid virus transmission during news covering process. Moreover, various media companies announce layoffs and salary cuts by asserting business uncertainty. This study aims to describe journalists’ vulnerability within journalism activity and journalist as occupation during the COVID-19 pandemic in 2020. This study was conducted with a qualitative method by analyzing the primer data from 50 journalist various region and representatives of journalist’s association in Indonesia. Furthermore, we analyze secondary data that provided officially by Alliance of Independent Journalists Indonesia. Authors found that the lack of health insurance, support for preventing the spread of COVID-19, unilateral dismissals by media institutions, and salary cuts place journalists in a difficult position. Aspects of journalism activities that run normally without institutional or structural support legitimize the vulnerabilities experienced by journalists in Indonesia.